Decorin is down‐regulated in multiple myeloma and MGUS bone marrow plasma and inhibits HGF‐induced myeloma plasma cell viability and migration1. (7th July 2013) - Kristensen, Ida B.; Pedersen, Lise; Rø, Torstein B.; Christensen, Jacob H.; Lyng, Maria B.; Rasmussen, Lars M.; Ditzel, Henrik J.; Børset, Magne; Abildgaard, Niels
Abstract Objectives Decorin is a stromal‐produced small leucine‐rich proteoglycan known to attenuate tumour pro‐survival, migration, proliferation and angiogenic signalling pathways. Recent studies have shown that decorin interacts with the hepatocyte growth factor (HGF) receptor c‐Met, a potential key pathway in multiple myeloma (MM). Methods Decorin levels in paired peripheral blood and bone marrow plasma samples from healthy volunteers (HV) (n = 23), and patients with monoclonal gammopathy of undetermined significance (MGUS) (n = 41) and MM (n = 19) were determined by ELISA. Further, the ability of decorin to inhibit HGF‐induced effects on MM cell lines were analysed in vitro using cell viability and Transwell migration assays. Results We found that decorin concentrations were significantly higher (P < 0.05) in bone marrow (BM) plasma from HVs (median 35.2 ng/mL; range, 15.3–99.1) compared with MGUS (median 22.5 ng/mL; range, 11.1–59.5) and patients with MM (median 21.5 ng/mL; range, 10.6–35.9). Decorin levels were higher in BM plasma than in peripheral blood in all groups, with a BM/PB ratio of 3.9, 3.4 and 2.5 for HV, MGUS and MM, respectively. A positive correlation (Spearman's ρ = 0.51, P < 0.05) was found between simultaneously measured levels of HGF and decorin in BM plasma in HVs, but not in MGUS or MM samples. Functionally, decorin inhibited HGF‐induced migration and viability of INA‐6 and ANBL‐6 MM cell lines, independent of c‐Met down‐regulation. Conclusion Our results show that decorin is down‐regulated in MGUS and MM bone marrow plasma and that it inhibits HGF‐induced viability and migration of myeloma cell lines in vitro.